Development of teaching materials to support merdeka curriculum learning on periodic system materials for Phase E - Ruri Januarita; Mawardi Mawardi; Okta Suryani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This research on the development of teaching materials aims to develop teaching materials to support Merdeka Curriculum learning on the material of the periodic system of elements of Phase E to determine the validity of teaching materials to support Merdeka curriculum learning on the material of the periodic system of elements of Phase E based on the feasibility aspects of content, presentation, components linguistics, as well as graphical components, and knowing the user's response to teaching material products to support merdeka curriculum learning on periodic system elements of Phase E. The plump development model was used in this research procedure with the educational design research (EDR) research type. However, the research only reached the practicality stage. The development results show that the teaching materials are feasible to use correctly, with an expert assessment of the feasibility of teaching materials of 0.90. For user responses, teaching materials can be appropriately used, with a score of (93.7% teachers and 91.7% students).